ANALISIS KEBUTUHAN INSTRUMEN PENILAIAN BERBASIS HOTS PADA MATA KULIAH PENDIDIKAN IPS - Dian Eka Amrina; Deskoni; Edutivia Mardetini (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This study aims to analyze the need for HOTS-based assessment instruments in the social studies course. This research was conducted in a descriptive quantitative, with research samples, namely lecturers for the Social Studies subject and 56 Indralaya campus students class of 2019/2020, Economic Education Study Program, FKIP Sriwijaya University. The research data were obtained through interviews, documentation and questionnaires. From the results of the interview, it was obtained information about the items made not based on HOTS and not yet varied. Observations made on the final examination assessment instrument showed that 80% of the items were still focused on MOTS, and from the student answer sheets it could be seen that students were still answering questions from the memorization process. The results of the questionnaire obtained showed that 92.9% of students thought that in order to understand social science concepts it was necessary to make problem-solving questions that could train HOTS. So it can be concluded that lecturers and students need HOTS-based assessment instruments in the social studies course.